Nilai-Nilai Pendidikan Karakter Tentang Bersikap Sabar Pada Kisah Nabi Yusuf Dalam Al-Qur’an (Kajian Q.S. Yusuf Ayat 90) - Anisatun Novia Ariqoh; Ngarifin Ngarifin; Robingun Suyud El-Syam (Publikasi Indonesia, 2022)
The reason for doing this research is to know the idea of character training about the disposition of persistence in Islam, In the request to have the option of understanding the idea of a character school about the mentality of tolerance embodied in Q.S. Yusuf refrained 90, To know the execution of the working person from the mentality of the patient embodied in the narrative of the Prophet Joseph in the present. The methodology used in this article is a subjective methodology with a kind of writing research. The strategy of assortment of information uses documenter techniques and reads information online. The information obtained is obtained from important information and optional information. The fundamental information in this study is the Quran and the translated books, while the next information is books related to the school of characters about tolerance. The method of information examination in this study uses the procedure of understanding tahlili. The consequences of this study give the result that with respect to the Qur'an, yusuf chapter 90 in Islam itself has been shown about the personality of persistence, by giving this patient person through formal and relaxed schools. In educating and cultivating a patient person through an extraordinary methodology that leads to the internal force of the heart that moves the individual to apply the patient person who has been educated. The use of this patient person as an individual wisdom so as not to slip in carrying out the movements he will take.